The ark of nuh: quran stories for little hearts - Khan, Saniyasnain; Anand, Achla Anand, Achal K. (Goodword Books New Delhi, 2001)
The Ark of Nuh: Quran Stories for Little Hearts is an engaging children's book that narrates the story of Prophet Nuh (Noah) and his remarkable journey, teaching young readers about faith, obedience, and the importance of compassion in the face of adversity.